Efficient and Stable Quasi‐2D Perovskite Solar Cells Enabled by Thermal‐Aged Precursor Solution. (22nd September 2021) - Li, Xing; Li, Kang; Wang, Boxin; Zhang, Xuning; Yue, Shengli; Li, Yanxun; Chen, Qian; Li, Shilin; Yue, Tong; Zhou, Huiqiong; Zhang, Yuan
Abstract: Quasi‐2D perovskites have received wide attention in photovoltaics owing to their excellent materials robustness and merits in the device stability. However, the highest power conversion efficiency (PCE) reported on quasi‐2D perovskite solar cells (PSCs) still lags those of the 3D counterparts, mainly caused by the relatively high voltage loss. Here, a study is presented on the mitigation of voltage loss in quasi‐2D PSCs via usage of thermal‐aged precursor solutions (TAPSs). Based on the (AA)2 MA4 Pb5 I16 ( n  = 5) quasi‐2D perovskite absorber with a bandgap of ≈1.60 eV, a record‐high open‐circuit voltage of 1.24 V is obtained, resulting in boosting the PCE to 18.68%. The enhanced photovoltaic performance afforded by TAPS is attributed to the thermal‐aged solution processing that triggers colloidal aggregations to reduce the nucleation sites inside the solution. As a result, formation of high‐quality perovskite films featuring compact morphology, preferential crystal orientation, and lowered trap density is allowed. Of importance, with the improved film quality, the corrosion of Ag electrode induced by ion migrations is effectively restrained, which leads to a satisfactory storage stability with <2% degradation after 1200 h under nitrogen environment without encapsulation. Abstract : Thermal‐aged precursor solution (TAPS) featuring the aggregated colloidal clusters with fewer nucleation sites is applied to fabricate high‐quality quasi‐2D perovskite films, through which a record‐high V OC of 1.24 V is achieved in (AA)2 MA4 Pb5 I16 ‐based quasi‐2D perovskite solar cells, leading to a champion efficiency of 18.68%.